Implementation Of MEE (Madical, Education, Eco-Tourism): A Strategy For Collaborative Forest Management In Meru Betiri National Park - Kurniawan, Andik; Manan, Abdul; Santoso, Budi (Graduate School, Universitas Brawijaya, 2014)
Global issues of greenhouse effect include the depletion of the ozone layer and the increases surface temperature. Response to these issues is attempted to empower and enhance the role of community participation in sustainable and equitable forest resource management. Since 1993, Indonesian NGO Konservasi Alam Indonesia Lestari (KAIL) starts empowering the forest buffer community with MEE (Medical, Education, Ecotourism) site model. Purpose of this paper is to describe the model of MEE in empowering forest buffer communities, describe the ecological, economic and social impact of the model, and describe the collaborative forest management. The strategies of community empowerment with MEE in Meru Betiri forest rehabilitation zone improvem the forest ecology. The success of MEE site model reduces negative perceptions on communities that have less conservation awareness. Community-based forest resources management need to integrate ecological and economic value in achieving forest conservation and community's welfare. Keywords: MEE (medical, education, eco-tourism), forest management, Meru Betiri National Park